Dr. Emerita Quito was awarded the Professorial Chair in Humanities - Quito, Emerita S. (Animo Repository, 1980)
Dr. Emerita Quito was awarded the Professorial Chair in Humanities in 1980. She has been awarded the decoration Chevalier dans l'Ordre des Palmes Academiques by the Government of France and was invited by the French Government to teach Philosophy in a French University. She was founder and president of the Phil. Academy of Philosophical Research.